Human factor development through Ngoma Buntibe among the BaTonga of Binga: the case of Sinakoma ward - Mutale, Didmus (Midlands State University, 2017)
The research focuses on human factor development through Ngoma Buntibe performance among the BaTonga of Binga district, particularly of Sinakoma ward. It explores the Ngoma Buntibe performance in the process unravelling human factor development through the performance. The study is basically qualitative but it also employs some quantitative techniques. Similarly the study uses data collection methods that included semi-structured interviews, questionnaires and document analysis in gathering data from Ngoma Buntibe performers and academics. Afrocentricity was adopted to inform arguments and analysis of this study. The research observes that the Ngoma Buntibe performance mainstreams human factor development in all the occasions it is performed. The occasions on which Ngoma Buntibe music is performed includes memorial services, chief installation ceremonies and harvest celebration galas. As such, the Ngoma Buntibe performance has been viewed as an important African initiative as it permeates all the aspects of life of the BaTonga. To this effect, the study also establishes the various values that are embodied within the Ngoma Buntibe performance which include the impartation of life skills, moral values and the community’s knowledge base among other values. However, some of the values that are transmitted through harvest celebration and galas are at stake due to the occasion’s exposure to adversity like aridity facing the Binga district. As such the Ngoma Buntibe performances for galas is seldom conducted. Therefore the study concludes that despite adversity Ngoma Buntibe performance play an integral part in Human factor development.